Resistance Training Has an Effect on Lowering Insulin Resistance Based on HOMA IR Examination in Poly Cystic Ovarian Syndrome (PCOS) Patients: Meta-Analysis - Nasution, Muhammad Solih; Akbar, Aidil (Universitas Muhammadiyah Sumatera Utara, 2025)
Abstract: Poly Cystic Ovarian Syndrome (PCOS) is a complex endocrine disorder that affects women of reproductive age. Insulin resistance, obesity, and hormonal imbalances are the main characteristics of this condition. Physical exercise, including weight training or resistance training , is suspected to be effective in lowering insulin resistance, but direct comparisons based on the results of the HOMA IR examination have not been carried out systematically. This meta-analysis aimed to evaluate the effectiveness of weight training in lowering insulin resistance based on the results of the HOMA IR examination in PCOS patients. Four clinical studies that met the inclusion criteria and included 87 women diagnosed with PCOS and 93 women without PCOS were analyzed for their insulin resistance conditions. Insulin resistance check parameters using the HOMA IR test. Statistical analysis using a fixed effect model with a paired t test. Overall, resistance training interventions showed a negative effect on the difference in HOMA-IR between pre-test and post-test. The mean HOMA-IR score after the intervention was lower compared to the pre-intervention score. This suggests that resistance training can lower insulin resistance in PCOS patients. Resistance training can reduce insulin resistance in PCOS patients as measured by HOMA-IR examination. However, variations in results between studies suggest that the effects of resistance training on insulin resistance are not entirely uniform, depending on factors such as exercise intensity, duration, and characteristics of study participants.